RELIGIOSITY, RELIGIOUS COPING AND THE PSYCHOLOGICAL WELL-BEING OF LATINO CAREGIVERS. (11th November 2018) - Gonyea, J; O'Donnell, A; Mitchell, S; Lopez, L
Abstract: By 2050, the older Latino population will reach 17.5 million and constitute 20% of the nation's seniors; correspondingly, the Alzheimer's disease rate among Latinos is projected to increase 1.3 million. Consequently, there is growing interest in delivering culturally sensitive health care services to this population, Although a significant body of research exists exploring how personal resources may moderate the impact of caregiving stressors on caregiving well-being; there is relatively little research on the role of religiosity and religious coping in influencing caregiver mental health outcomes. This knowledge gap is significant given evidence suggests that Latinos more often use religion and spirituality as a coping mechanism than Anglos. In this study, we explored the association of religiosity and religious coping with measures of caregiver depression and anxiety among 67 Latino Alzheimer's caregivers through in depth interviews conducted in Spanish in the caregiver's home. Our core measures included the Duke Religiosity Index; Pargament's Brief RCOPE which taps positive and negative religious coping methods, the CES-D Depression Scale and the State Anxiety Inventory-State Scale (STAI-S). Our regression analysis revealed that, after controlling for caregiver and care recipients demographic and health variables, negative religious coping predicted greater levels of depression and anxiety. The study suggests that religion provides some persons with a framework for interpreting the challenges associated with caregiving and that negative religious coping methods can have deleterious effects on psychological well-being. The implications for primary care providers regarding how to address the spiritual concerns of Latinos and other ethnic minorities are discussed.